Integrative Transcriptomic and Metabolomic Analysis Reveals the Molecular Mechanisms Underlying Flowering Time Variation in Camellia Species - Ling Zhou; Tao Guo; Shihui Zou; Lingli Li; Xuemei Li; Jiao Wang; Zilin Zhu; Lijiao Ai (Agronomy, 2025)
Camellia’s ornamental value is constrained by its natural winter–spring flowering period. Although the discovery of Camellia azalea provides important germplasm resources for developing cultivars with year-round flowering, the molecular mechanisms underlying flowering time variation remain unclear. Here, we investigated three germplasms with distinct flowering patterns: winter–spring flowering Camellia japonica ‘Tieke Baozhu’, summer–autumn flowering Camellia azalea, and their hybrid Camellia ‘Lingnan Yuanbao’ inheriting the latter’s flowering traits. Integrated transcriptomic and metabolomic analyses revealed that differentially expressed genes (DEGs) and metabolites (DAMs) were mainly enriched in the pathways related to photoperiod regulation, plant hormone synthesis and signal transduction and flavonoid synthesis. The transcription factor (TF) analysis revealed that the bHLH and MYB TF families were significantly differentially expressed in different Camellia germplasm, suggesting their potential involvement in the regulation of flowering time through the plant hormone signal transduction and photoperiod pathway. Meanwhile, photoperiod regulation related genes, including Cryptochrome circadian regulator (CRY), Timing of CAB expression 1 (TOC1), and phytochrome interacting factor 3 (PIF3), showed significant expression differences, further confirming the photoperiod pathway’s crucial regulatory function. In terms of plant hormone levels, there were significant differences in the levels of gibberellin (GA), abscisic acid (ABA), and jasmonic acid (JA) among Camellia germplasm. The differential expression characteristics of DELLA (Asp-Glu-Leu-Leu-Ala) proteins indicated that the GA signal transduction pathway was one of the key factors regulating flowering time in Camellia. Additionally, metabolomics analyses showed significant differences in flavonoid metabolite content among Camellia germplasm, which was significantly correlated with the different developmental stages of the buds. Our findings provide a theoretical basis for the molecular breeding of everblooming Camellia cultivars, advancing the understanding of flowering regulation mechanism in ornamental species.